Transgressive Romanticism - Peer, Larry H. (Cambridge Scholars Publishing, 2018)
"Romanticism is an intuitive grasp of the self and the other in an interdependent imperative, non-systematic, transcendent, radically individuated, and endlessly interconnective. The set of norms Romanticism represents and broadcasts, therefore, lends itself particularly well to interdisciplinary and cross-linguistic study, essentially demanding a view coming from and constructed out of more than one discourse field. These norms radically transgress not only the cultural and literary inheritance of thinkers and artists beginning in the late eighteenth century, but do so in a transnational and comparative way unique in Western history. This collection of essays, bringing together established scholars and newer academic voices, offers fresh perspectives on what Romanticism thought itself to be by suggesting spaces in Romanticism studies needing negotiation and elaboration. Presenting a protocol that escapes the circular referentiality of Romanticism studies typically limited to one academic discipline or one language area, this volume works through topics and ideas including Hegelian reflections, lyric poetry, stage drama, music, political implications, and even vampires, outlaws and zombies."--